2007
DOI: 10.4314/ejhd.v21i2.10039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status of preschool children of Gumbrit, North West Ethiopia

Abstract: Background: Economically Ethiopia remains one of the poorest countries in the world and malnutrition is one of the major and most pressing health problems; especially among children. Objective: To assess the nutritional status of preschool children in a rural locality of Northwest Ethiopia Methods: A cross-sectional survey was conducted in a rural locality called Gumbrit. Weight and height of the study children were measured and the socio-demographic characteristics of the subjects were collected using a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
48
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 5 publications
21
48
4
Order By: Relevance
“…In a study done in rural localities of NorthWest Ethiopia, preschool children who belonged to families with low income were at greater risk of being wasted, underweight and stunted. [21] Another factor possibly contributing to the high poverty levels observed in the current study could be the high level of illiteracy (17% of caregivers), which is comparable with other studies conducted in SA [3] and rural Uganda. [22] A low literacy rate can contribute to caregivers getting low paying jobs, resulting in low income when compared with their counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…In a study done in rural localities of NorthWest Ethiopia, preschool children who belonged to families with low income were at greater risk of being wasted, underweight and stunted. [21] Another factor possibly contributing to the high poverty levels observed in the current study could be the high level of illiteracy (17% of caregivers), which is comparable with other studies conducted in SA [3] and rural Uganda. [22] A low literacy rate can contribute to caregivers getting low paying jobs, resulting in low income when compared with their counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…The result is similar to studies conducted in Somali region [12], Ethiopia, Oromia region West Ethiopia [14], and Gambit, Ethiopia [9]. Similarly, other studies conducted in Iran [6], Nigeria [7], north Sudan [10] and Zimbabwe [11] argued that low family income was the risk factor for under five acute malnutrition.…”
Section: Discussionsupporting
confidence: 86%
“…Evidence showed that socio-demographic factors such as; household's poverty and income, residence, parental occupation, parental education, maternal age, family size, overcrowding, and lack of exposure to mass media have influenced the occurrence of underfive acute malnutrition [4][5][6][7][8][9][10][11][12]. Furthermore, some behavioral or community factors including lack of maternal and child health services, of adequate and safe water supply, hygiene of caregiver and of improved environmental sanitation play their role in the occurrence of malnutrition [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of underweight in this study was lower as compared with EDHS 2011 (29%), Amhara region (28.5%), Tigray region [38.3%], and Western Kenya [30%] [8,[10][11][12][13]. This difference may be due to the attribution of season.…”
Section: Discussionmentioning
confidence: 56%